Self-employed individuals, time use, and earnings - Konietzko, Thorsten (Journal of Family and Economic Issues, 2015)
This paper analyzes the time allocation of self-employed individuals and the impact of housework activities on earnings of self-employed individuals. In contrast to men and women in paid employment time allocation of self-employed individuals was more gendered with men performing more market work. Also differences in daily routine of activities occurred. While descriptive statistics and pooled OLS earnings regressions indicated a negative correlation between time spent on housework activities and earnings, fixed effects earnings regressions only showed a significantly negative impact on monthly earnings of self-employed men. This impact disappeared after controlling for potential endogeneity via instrumental variable estimator
Keywords: Self-employment; Time use; Earnings; Gender earnings gap; Germany

The Effect of Housework on Wages in Germany: No Impact at All - Hirsch, Boris; Konietzko, Thorsten (Journal for labour market research, 2013)